The Psychological, Behavioral, and Educational Impact of Immigration: Helping Recent Immigrant Students to Succeed in North American Schools - McIntyre, Thomas; Barowsky, Ellis I.; Tong, Virginia (Journal of the American Academy of Special Education Professionals, 2011)
Educators’ lack of knowledge of the cultural and immigration overlays on behaviors presents a quandary. It makes it difficult, given the present state of assessment in this area, to determine whether an emotional or behavioral disorder exists, or whether the behavior is acceptable to the newcomer’s culture and therefore reflects a cultural marker. This article addresses factors to be considered in making this differentiation, and provides information and guidance in meeting the psychological, emotional, and social needs of recent immigrant students.